COMMUNITY INFORMATION SYSTEMS: URGENCY AND CHALLENGES IN DEVELOPMENT - IN THE PERSPECTIVE OF SPACE TRANSITION THEORY - Yuni Sri Dwijayanti; Iqrak Sulhin (Polteknik Ilmu Pemasyarakatan, 2019)
This journal discusses Correctional Information Systems as a system that produces information from systems that work manually transitioning to computeized and online system. Correctional information system is essentially generated from fact-sourced data that is developed into information. In its development, the penal information system also developed along with the times. The Correctional System Database that has been utilized by the Directorate General of Corrections is a material for researchers to see the urgency and challenges in the development of correctional information systems at this time. The complexity of the tasks and functions of correctional requires good data management. Fact or evidence as data are collected, processed to produce information for decision making/leadership policies. This research is a qualitative research with exploratory type. Data merging technique used is the study of literature, interviews with Delphi techniques with expert speakers. The results of this study indicate the fact that there is a transition to the development of correctional information systems from several aspects (based on functions). Constraints greater than human resources. The purpose of the emergence of correctional information system is the challenges faced and the problems that will arise due to the prevention of information generated from the system.